Methods of children’s voice development in music culture lessons - M.Djumaboyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the genre and types of children’s songs in music lessons and the methods of children’s voice development.